Activity and stability of biochar in hydrogen peroxide based oxidation system for degradation of naphthenic acid. (February 2020) - Devi, Parmila; Dalai, Ajay K.; Chaurasia, S.P.
Abstract: This study investigated the stability and catalytic activity of wheat straw biochar (WS), hardwood biochar (HW) and commercial activated carbon (AC) in hydrogen peroxide (H2 O2 ) based oxidation system for degradation of model naphthenic acids compound, 1-methyl-1- cyclohexane carboxylic acid (MCCA). WS showed excellent catalytic activity for decomposition of H2 O2 and MCCA degradation as demonstrated by high H2 O2 decomposition rate (2.0*10 −4  M −1 s −1 ), amount of hydroxyl (OH) radicals generated (182 mg/L) and degradation efficiency of MCCA (100% at Co – 100 mg/L). 2-Methyl pentatonic acid was identified as reaction intermediate and 99% mineralization of MCCA was obtained within 4 h. The real wastewater conditions were simulated by addition of chloride (Cl − ) and bicarbonate ions (HCO3 − ) and found that lower concentrations of Cl − and HCO3 − have minimal influence on MCCA removal. Overall, biochar catalyzed H2 O2 based oxidation process has great potential and can be applied for degradation of NAs in oil-sand processed water. Graphical abstract: Image 1 Highlights: Biochars demonstrated excellent catalytic activity for decomposition of H2 O2 . Surface chemistry of biochars is main driving force behind decomposition of H2 O2 . Hydroxyl (OH) radicals were the main radical responsible for MCCA degradation. 2-methyl pentatonic acid was identified as reaction intermediate. Biochars were more stable towards chemical oxidation and surface weathering than AC.